Library anxiety among postgraduates: A preliminary study - Sinnasamy, Janaki; Mohamad Amin, Ratnawati Sari (Persatuan Pustakawan Malaysia, 2015)
A preliminary study to investigate the prevalence of library anxiety among postgraduates who attended the information skills instruction sessions at a public university in Malaysia was carried out. The mode and module of these sessions had undergone minimum changes since it was first started. Brief questionnaires to assess these sessions usually indicate moderate satisfaction. It was necessary to find out students’ needs and anxious areas before steps can be taken to facilitate the continual improvement of these sessions. The modified Library Anxiety Scale was distributed to the students who attended the sessions. The objective of this study was to assess the prevalence of library anxiety among these students and to explore the item statements in the dimensions which can give an insight to the unspoken anxieties of these students. It was revealed that generally, postgraduates in this study are not really anxious about library staff and services barriers as the mean level for both factors is below average but factors associated with affective barriers and library resources barriers show a slightly elevated mean level of anxiety. Statements such as I am unsure how to begin my research and I get confused trying to get my way around the library were statements identified as the reasons for a great source of library anxiety. It is strongly recommended that besides hands-on during these sessions, students have to be brought around the library and also taught the effective strategies to begin research.